Effects of Olive Leaf Extract on Prevention of Molecular, Histopathological, and Enzymatic Changes in Chicken Carbon Tetrachloride-Induced Liver Damage: - Vahidi-Eyrisofla, Nazila; Hojati, Vida; Yazdian, Mohammad-Reza; Zendehdel, Morteza; Shajiee, Hooman (Galen Medical Journal, 2019)
Background: Today, the use of additives such as antibiotics and growth hormones that increase production efficiency in breeding broiler chickens has become inevitable. However, the use of such additives and antibiotics associated with side effects such as liver damage. Oxidative stress occurs due to an imbalance between oxidants and antioxidants. Studies have shown that olive leaves have an antioxidant effect on free radicals. This study was to evaluate the possible effect of olive leaf extract on carbon tetrachloride (CCL4)-induced liver damage (molecular and tissue) and changes of enzymes in chickens. Materials and Methods: A total of 50 chickens were used and classified into5 groups. Treatment groups received 0.5, 1, and 1.5 mg/kg of the olive leaf extract from day 21 of the experiment. Two control groupshealthy and poisoneddid not receive any extract. On the day 35 of the experiment, 1cc of CCL4 was dissolved with olive oil and injected intraperitoneally into the experimental and poisoned control groups. Blood and liver tissue sampling were performed. Results: The histopathology results showed that at high doses of olive leaf extract, the cells and vessels were regularly curable, and sinusoids were healthy. The expression of B-cell lymphoma 2 (BCL2) increased, and that of BH3 interacting domain death agonist (BID)decreased. Enzymatic tests, including serum glutamic-oxaloacetic transaminase, serum glutamic-pyruvic transaminase, alkaline phosphatase, gamma-glutamyl transpeptidase, showed a reduction in BID expression in the experimental group compared with the control group(P<0.005). Conclusion: We concluded that olive leaf extract boosts the BCL2—an antiapoptotic gene—and reduces BID—an apoptosis gene—in the liver of chicken. It prevents the liver cells from disintegrating and destroys sinusoids and liver blood vessels. The high doses of the olive leaf extract caused liver resistance to CCL4 toxicity in chicken. [GMJ.2019;8:e1204]